Vpliv prepričanj uporabnikov na njihova stališča do marketinškega komuniciranja na družbenih omrežjih - Tomše, Denis (Akademija MM, 2012)
Social networks are becoming an important marketing communication channel. Previous studies examined the impact of particular users' beliefs about certain factors on their attitudes towards advertising and web advertising, but little is known about the impact of users' beliefs about certain factors on their attitudes and behavior towards marketing communication in social networks. This paper shows that users' beliefs about personal factors (product information, hedonic pleasure and social image) as well as their beliefs about the social factor "good for economy" have a positive impact on the attitudes towards marketing communication in social network, while users' beliefs about the social factors "falsity/no sense" and "value corruption" have a negative impact. Beliefs about factor "materialism" were not statistically significant. Users' attitudes toward marketing communication on social networks have a positive impact on users' behavior towards marketing communication in social networks. The results send a clear message to marketing professionals to adapt their messages in social networks in order to give utmost information about products, to be amusing and to emphasize the reputation of their products. On the other hand, they should minimize messages with regard to which the individual user could assume that they corrupt values, have too much reference to eroticism and/or contain negative manipulation.
Keywords: communication; družbena omrežja; komuniciranje; marketing; svetovni splet; trženje